2016
DOI: 10.1177/0969733015624486
|View full text |Cite
|
Sign up to set email alerts
|

Violence against new graduated nurses in clinical settings

Abstract: This study provided the context for identifying details of various types of workplace violence against new graduated nurses. It should be approached as a health system priority that requires specific multi-dimensional methods to manage consisting of identification, strategic planning, policymaking, prevention, education, and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
1
21
0
2
Order By: Relevance
“…Forms of horizontal violence are widely, in Ebrahimi's study [8], horizontal violence was classified into three categories, including psychological violence, verbal violence and physical violence. Domestic study [9]…”
Section: The Forms Of Horizontal Violencementioning
confidence: 99%
“…Forms of horizontal violence are widely, in Ebrahimi's study [8], horizontal violence was classified into three categories, including psychological violence, verbal violence and physical violence. Domestic study [9]…”
Section: The Forms Of Horizontal Violencementioning
confidence: 99%
“…Subtle forms of violence, such as gossip about private life or work done, are not recognized as such or as a violation of privacy, although they are far from the principles and values that characterize professional conduct. 4 The interviewees reported that those nurses who use forms of violence do it to mask their professional insecurity and personal emptiness, which can be confirmed by the theory of the Oppressed Group Behaviour , considered a risk factor for horizontal violence. 29 Low self-esteem and feelings of helplessness, recalled by the narratives of new graduates, portray nurses as an oppressed group, as also reported by Ebrahimi.…”
Section: Discussionmentioning
confidence: 72%
“…Horizontal violence has been described as ‘a negative interaction, an interpersonal conflict between two nurses of similar positions, same hierarchical levels’, 3 and it may be psychological, verbal, physical or characterised by discrimination, prejudice and insufficient support. 4 Its impact on nurses’ well-being is greater than when it is perpetrated by patients or their family members, referred to as ‘external’, especially if it manifests itself under psychological and verbal forms. 5 Among the various definitions that have described this phenomenon in the literature, there is its association with bullying, considered as an event that is perpetuated over time, as opposed to horizontal violence that may occur also occasionally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the study noted that self-esteem describes the individual's believes on his/her capability (Pierce et al, 2015). Nurse's self-esteem involves the real self, empathy, ability to cooperate with colleagues (Ebrahimi et al, 2016). Thus, the person with higher self-esteem consider himself as the person of worth (Rosenberg, 1979).…”
Section: Literature Reviewmentioning
confidence: 99%